Flora and vegetation of some coastal ecosystems of Sterea Ellas and eastern continental Greece - Sarika, Maria (Lazaroa, 2012)
Vegetation of four coastal ecosystems of eastern continental Greece and of Sterea Ellas, including dune, marshland, wet meadow, reed bed and aquatic habitats, was studied in several years. The flora of the investigated regions consists of 217 taxa belonging to 42 families and 135 genera, most of which are reported for the first time. The majority of taxa are Therophytes (101 taxa, 46%); Hemicryptophytes and Geophytes are also well represented in the life form spectrum. From a chorological point of view the Mediterranean element (123 taxa, 57%) outweight the rest while the most diverse group of widespread taxa occupies the second place (83 taxa, 38%). The macrophytic vegetation was analysed following the Braun-Blanquet method. Twenty one plant communities were found belonging to twelve alliances, ten orders and eight phytosociological classes. The vegetation units distinguished are described, documented in form of phytosociological tables, and compared with similar communities from other Mediterranean countries. According to directive 92/43/EU, nine habitat types were delimited through the assessment of the dominant vegetation types.